Analisis Tingkat Kesehatan Perbankan Dengan Metode Rgec (Studi Pada Bank Umum Swasta Nasional Devisa Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020) - Fedencia Lovica Serlli Avelani; Galuh Budi Astuti (Universitas Katolik Widya Karya Malang, 2022)
It is necessary to assess the level of banking soundness to provide information and maintain public trust. Assessment of banking soundness level has been regulated in OJK regulation No 4/POJK.03/2016. OJK Regulation No. 4/POJK.03/2016 states that commercial banks in Indonesia are required to evaluate the health of each bank using the RGEC method, namely the Risk Profile to assess the risks faced by banks that are quantitative or qualitative, Good Corporate Governance (GCG). to evaluate bank governance according to predetermined principles, Earning to evaluate the ability of banks to earn company profits and Capital to measure the quality of the bank's capital. This study aims to assess the soundness of foreign exchange national private commercial banks listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period using the RGEC method. This type of research is a case study. The population in this study amounted to 22 banks. The sampling method used purposive sampling and 8 banks were selected according to the established criteria. The data source used is secondary data from annual reports published on the IDX during the period studied using the data collection method, namely documentation. The data analysis technique in this study is descriptive quantitative.